My life - Clinton, Bill, 1946- (New York : Knopf, 2004)
In this autobiography, President Bill Clinton portrays himself as a global leader who decided early in life to devote his intellectual and political gifts, and his extraordinary capacity for hard work, to serving the public
Includes index.
Keywords: Clinton, Bill, -- 1946-; Clinton, Bill, -- 1946- -- Family; Clinton family; Presidents -- United States -- Biography; United States -- Politics and government -- 1993-2001.